2008
DOI: 10.1371/journal.pone.0002174
|View full text |Cite
|
Sign up to set email alerts
|

Protein Folding Activity of Ribosomal RNA Is a Selective Target of Two Unrelated Antiprion Drugs

Abstract: Background6-Aminophenanthridine (6AP) and Guanabenz (GA, a drug currently in use for the treatment of hypertension) were isolated as antiprion drugs using a yeast-based assay. These structurally unrelated molecules are also active against mammalian prion in several cell-based assays and in vivo in a mouse model for prion-based diseases.Methodology/Principal FindingsHere we report the identification of cellular targets of these drugs. Using affinity chromatography matrices for both drugs, we demonstrate an RNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 56 publications
(81 reference statements)
5
73
0
1
Order By: Relevance
“…Is PFAR functional in the modern cells, or is it an evolutionary relic representing function of an ancient protein production machine? Although there are few reports of PFAR in living bacterial cells (14,15), the in vivo context of PFAR has not been fully established. However, one recent finding has linked PFAR to living cells and also associated it with diseases of higher eukaryotes.…”
Section: Domain V Of the 23s/25s/28s Rrna Of The Large Ribosomal Subumentioning
confidence: 99%
See 3 more Smart Citations
“…Is PFAR functional in the modern cells, or is it an evolutionary relic representing function of an ancient protein production machine? Although there are few reports of PFAR in living bacterial cells (14,15), the in vivo context of PFAR has not been fully established. However, one recent finding has linked PFAR to living cells and also associated it with diseases of higher eukaryotes.…”
Section: Domain V Of the 23s/25s/28s Rrna Of The Large Ribosomal Subumentioning
confidence: 99%
“…However, one recent finding has linked PFAR to living cells and also associated it with diseases of higher eukaryotes. It has been shown that the two unrelated compounds 6-aminophenanthridine (6AP) and guanabenz acetate, with demonstrated activity against yeast ([PSI ϩ ] and [URE3]) and mammalian prions, bind to rRNA and inhibit PFAR (15)(16)(17). The correlation between the antiprion activity of these two drugs and their ability to specifically inhibit PFAR suggests that PFAR could be involved in the establishment or maintenance of the prion processes in cells.…”
Section: Domain V Of the 23s/25s/28s Rrna Of The Large Ribosomal Subumentioning
confidence: 99%
See 2 more Smart Citations
“…L'approche la plus fructueuse fut la chromatographie d'affinité sur composés immobilisés sur des billes de Sépharose®. Cette approche nous a permis d'identifier l'activité chaperon de protéines du ribosome (PFAR, protein folding activity of the ribosome) comme nouvel acteur potentiel de la « prionisation », et donc comme cible thérapeutique potentielle pour traiter ces maladies [27][28][29]. Tous travailler avec le prion de mammifère, les prions de levure peuvent être manipulés sans précaution particulière du fait de leur innocuité.…”
Section: Revuesunclassified